The Impact of Guarda Nacional Republicana’s Reward Systems on the Military’s Organizational Commitment - da Silva, Ariana Barra; Comba Lopes, Helga Santa; Rosado, David Pascoal (Journal of Reviews on Global Economics, 2020)
The aim of this research is to analyze the impact of Guarda Nacional Republicana’s rewards systems on the military’s organizational commitment and, more precisely, on intrinsic rewards. Organizations in general, but they also have a hierarchical structure like this, to achieve success, need to know what is most valued by workers, in this case, the level of intrinsic rewards, as a way to increase commitment. This analysis is important because of the need for the superior hierarchical structure to gauge which intrinsic rewards are most valued by their subordinates, as well as what kind of intrinsic rewards have the greatest impact on military commitment. Organizations intend to keep their employees engaged in an affective and normative way, as these are the components of commitment that have the most positive effects. In this research, questionnaires were applied to military personnel who work in Guarda Nacional Republicana Units located in the Lisbon district. The sample studied is constituted of 497 military. The results indicate that the granting of intrinsic, formal and informal rewards to the military produces positive effects on their commitment. That is, the relationship and impact between these rewards and the affective and normative components of commitment is significantly positive. In addition, the informal intrinsic rewards are the most valued by the military. We also conclude that the intrinsic rewards granted to the military are extremely important because they contribute to their maintenance in the organization. The present investigation can also help the hierarchical superiors, in their daily routine, to know how to make their subordinates more committed.